Immediate loading in partially edentulous patients with fixed implant-supported restorations cases report - Wang, Shuang; Duan, Siyi; Chen, Rui; Wang, Zijian; Tang, Yulong (Frontiers in Oral Health, 2024)
Objectives: This article reports on four rare cases involving multiple trauma-induced adjacent missing anterior teeth in the maxillary or mandibular region. These cases were successfully treated using a 4axial implant-based alternative insert and an immediate loading protocol. Material and methods: This series of cases was summarized by retrospective study that 4 patients who received a total of 20 immediately loaded implants. These patients had suffered from trauma-induced loss of 8-9 adjacent anterior teeth. The 4-axial-implants were inserted with the assistance of digital pioneer drill guides. The surgical procedure involved alveolar bone trimming or ultrasonic osteotomy, eliminating the need for traditional large-area bone augmentation. Pre-and post-operative CBCT was matched using DTX Studio Implant software, the deviation of implant between actual position and preoperative design was measured and compared using SPSS software package.The average follow-up duration 48 months after implant prostheses, the cumulative retention rate of the implants was 100%, the marginal bone loss averaged 0.53 mm (SD 0.15 mm), and buccal plate bone loss averaged 0.62 mm (SD 0.41 mm). Conclusions: This retrospective clinical report demonstrates the successful treatment of several patients with multiple adjacent maxillary or mandibular anterior teeth using four implant-supported screws to fix the frame and employing immediate loading. The approach resulted in long-term stable clinical outcomes. Moreover, the method not only shortens the period of edentulism but also facilitates easy disassembly, maintenance, and cleaning. Consequently, it emerges as a highly favorable clinical option for patients suffering from extensive tooth loss.